Snacking pattern of college students in Saudi Arabia: a cross-sectional study - Israa M. Shatwan (BMC Nutrition, 2022)
Abstract Background Although unhealthy snack foods are commonly consumed by college students, snacking patterns among college students have not been comprehensively examined in Saudi Arabia. In our study, we aimed to investigate snacking patterns among Saudi college students and to assess sociodemographic data that affect adherence to these snacking patterns. Methods Between January 2021 and March 2021 in Jeddah, Saudi Arabia, an online survey was conducted with 662 college students from a Saudi university. The survey included sociodemographic questions and a short food frequency questionnaire (FFQ) regarding the consumption of common snack foods. Snacking patterns were generated from the FFQ using the factor analysis method. Results Factor analyses generated seven snacking patterns, which explained 64.5% of the variance in snacking. Students in their early academic years (1–3 years) had a higher score for the convenience snack and fast-food pattern (0.22 ± 0.48 and 0.31 ± 0.52, respectively) than senior students (4–6 years) (P = 0.03 and 0.04, respectively). Healthy snacks patterns were higher among students at higher income levels (P = 0.006) and active students (P < 0.001) than among students at low- or mid-income levels and inactive students. Higher adherence to the beverages pattern was observed among male students (P = 0.03), active students (P = 0.01), and students with obesity than their counterparts (P = 0.02). The dairy products pattern was higher among male students (P = 0.04), students at higher income levels (P = 0.04), and students with obesity (P = 0.03) than their counterparts. Conclusions Most snacking patterns identified among the study participants were considered unhealthy. Adherence to healthy snacks is influenced by physical activity and family income. These findings may be helpful in the future for developing adequate nutrition education programs that promote health by adhering to healthy snack choices in this critical age group. Further studies are needed to confirm these findings and to investigate snacking patterns among other age groups in Saudi Arabia.